Survey on Digital Image Watermarking & Techniques (International Journal of Engineering and Computer Science, 2017)
In the past few decades Internet and digital technology has grown rapidly. The increasing and rapid advancement of Internet has made it extremely easy to send multimedia data accurate and fast to destination. It has provided various advantages like easy sharing of digital images, copying of digital images without quality degradation and editing of digital images. Also due to increasing trend of Internet, multimedia data is tend to duplicate and modify which makes multimedia security as an extreme concern to take care of. Modification and misusing of valuable data is very common and thus sending multimedia data to intended recipient has become more important. The problems arises includes privacy, corruption or processing of image and counterfeiting. This paper throws light on information hiding in order to protect original data from illegal duplication, distribution and manipulation through ”Digital Image Watermarking”. Watermarking is an art of hiding information into another file, which could be video, audio, text or image. The paper includes various type of watermarking, different techniques of watermarking.